Antiplatelet effects of clopidogrel and aspirin after interventional patent foramen ovale/ atrium septum defect closure. (18th May 2016) - Polzin, Amin; Dannenberg, Lisa; Sophia Popp, Valérie-; Kelm, Malte; Zeus, Tobias
Abstract: The optimal antiplatelet therapy after patent foramen ovale (PFO)/ atrium septum defect (ASD) closure is a matter of discussion. It is challenging as inter-individual responses to antiplatelet medication vary significantly and common complications are bleeding and ischemic events. In this study, we aimed to analyze the incidence of high on-treatment platelet reactivity (HTPR) to antiplatelet medication in patients undergoing PFO/ASD closure as well as clinical complications and thrombus formation on the occluder during six-month follow-up. This hypothesis generating pilot study was observed, which included 140 patients undergoing PFO/ASD closure. The primary endpoint was pharmacodynamic response to antiplatelet medication. A composite of death, myocardial infarction, bleeding, stroke and thrombus formation on the occluder during six-month follow-up was the secondary endpoint. HTPR to clopidogrel was analyzed using the vasodilator-stimulated protein phosphorylation (VASP), HTPR to aspirin by light-transmission aggregometry (LTA). In 71% of patients HTPR to clopidogrel was detected, HTPR to aspirin in only 4%. We observed 12 complications, 9 bleeding events (including 3 major bleeding events) and 3 transient ischemic attacks. No stroke and no thrombus formation on the occluder occurred. The primary endpoint was not associated with the secondary endpoint. The incidence of HTPR to clopidogrel in PFO/ASD closure patients is very high. Despite this high incidence, no stroke or thrombus formation on the occluder occurred at all. This leads to the hypothesis, that the benefit of additional clopidogrel medication is questionable and has to be investigated in large-scale clinical trials.